2017
DOI: 10.1155/2017/5020742
|View full text |Cite
|
Sign up to set email alerts
|

A Study on Organic Tomatoes: Effect of a Biostimulator on Phytochemical and Antioxidant Activities

Abstract: The objective of the present study is to investigate nutritional and antioxidant activity of four types of organic tomato cultivars. The differences in tomato quality are also tested between groups with or without treatment using an organic biostimulator, Stimplex. Total phenolic compounds (TPC), lycopene, -carotene, DPPH free radical scavenging activity, reducing power, and color parameters were investigated in the current study. The results showed that there was no significant difference in TPC among cultiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The increased value of RP due to plants treatments with biostimulants, determined in our study, is consistent with findings from the research conducted by Koleska et al (2017), who evaluated the antioxidative activity in tomato plants treated with a biostimulant based on free amino acids. In turn, the experiment carried out by Sidhu et al (2017) showed that tomatoes treated with a biostimulant in the form of a seaweed extract were characterized by a decreased reducing power compared to the control, irrespective of cultivar.…”
Section: Resultsmentioning
confidence: 99%
“…The increased value of RP due to plants treatments with biostimulants, determined in our study, is consistent with findings from the research conducted by Koleska et al (2017), who evaluated the antioxidative activity in tomato plants treated with a biostimulant based on free amino acids. In turn, the experiment carried out by Sidhu et al (2017) showed that tomatoes treated with a biostimulant in the form of a seaweed extract were characterized by a decreased reducing power compared to the control, irrespective of cultivar.…”
Section: Resultsmentioning
confidence: 99%
“…The same biostimulants were applied on cherry tomato plants and resulted in higher total phenol, ascorbic acid and lycopene content, as well as higher lipophilic antioxidant activity in fruits of treated plants (Caruso, De Pascale, Cozzolino, Cuciniello, et al, 2019), so they were suggested as an effective sustainable tool for enhancing tomato fruit yield and functional quality both under conventional and organic vegetable systems. An increment in lycopene and β‐carotene was obtained in organic tomatoes treated with Stimplex, the biostimulator based on A. nodosum extract, in the research of Sidhu, Nandwani, Wang, and Wu (2017). Chanthini et al (2019) evaluated seaweed extract (from the green seaweed Ulva flexuosa ) as a seed priming agent, towards the improvement of agronomic traits of cherry tomato, and reported positive responses in terms of enhanced seed germination capabilities and seedling vigour indices.…”
Section: Functional Foods Of Plant Origin: the Influence Of Abiotic Smentioning
confidence: 99%
“…Several important components like phytoene, lycopene, gamma-carotene, neurosporene and phytofluene are derived from tomatoes. The antioxidant property of lycopene helps to mitigate prostate cancer as well as other cardiovascular diseases (Sidhu et al 2017;Giovannucci et al 2002).…”
Section: Tomato (Solanum Lycopersicum)mentioning
confidence: 99%